1995
DOI: 10.1007/bf02779015
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization of DNA targets to glass-tethered oligonucleotide probes

Abstract: Hybridization of nucleic acids to surface-tethered oligonucleotide probes has numerous potential applications in genome mapping and DNA sequence analysis. In this article, we describe a simple standard protocol for routine preparation of terminal amine-derivatized 9-mer oligonucleotide arrays on ordinary microscope slides and hybridization conditions with DNA target strands of up to several hundred bases in length with good discrimination against mismatches. Additional linker arms separating the glass surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 18 publications
0
42
0
Order By: Relevance
“…Therefore, very often functional/active groups are introduced to either the 3Ј-end or 5Ј-end of oligonucleotides and solid supports to allow end-specific immobilization. However, these functional groups often cause a high degree of nonspecific binding during attachment (9,17,26) and even hybridization (26). For example, it has been reported that nonspecific attachment and nonspecific hybridization of oligonucleotides occurs on both aminosilane-modified (9) and epoxysilane-modified (26) surfaces, which are the two most commonly used silane-modified surfaces for DNA array preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, very often functional/active groups are introduced to either the 3Ј-end or 5Ј-end of oligonucleotides and solid supports to allow end-specific immobilization. However, these functional groups often cause a high degree of nonspecific binding during attachment (9,17,26) and even hybridization (26). For example, it has been reported that nonspecific attachment and nonspecific hybridization of oligonucleotides occurs on both aminosilane-modified (9) and epoxysilane-modified (26) surfaces, which are the two most commonly used silane-modified surfaces for DNA array preparation.…”
Section: Discussionmentioning
confidence: 99%
“…ODNs can be prepared by automated synthesis and then immobilized on surfaces in an array using many different methods with varying degrees of efficiency [14,15,16,17]. Arrays can also be created by in situ photolithographic techniques [18].…”
Section: The Problems Associated With Present Methods Of Probe Densitmentioning
confidence: 99%
“…Glass, quartz, silicon, platinum and gold are all good surfaces for sequence analysis using ODN arrays and binding of ODN molecules to the surfaces is easily accomplished [3,4,5,6]. …”
mentioning
confidence: 99%
“…[58][59] The relative excess of DNA on the particle compared to the surface aids the chances of successful hybridisation. The exact number of bound molecules hybridising is difficult to estimate as it will be influenced by, among other things, particle curvature at the point of contact, crowding from other adjacent molecules, and exact density of the DNA on both the surface and the particle at the point of contact.…”
Section: Dna Binding Of Individual Nanoparticles To the Surfacementioning
confidence: 99%